2017
DOI: 10.1038/s41598-017-16639-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement of a brain-computer interface using high-density multi-distance NIRS

Abstract: This study investigated the effectiveness of using a high-density multi-distance source-detector (SD) separations in near-infrared spectroscopy (NIRS), for enhancing the performance of a functional NIRS (fNIRS)-based brain-computer interface (BCI). The NIRS system that was used for the experiment was capable of measuring signals from four SD separations: 15, 21.2, 30, and 33.5 mm, and this allowed the measurement of hemodynamic response alterations at various depths. Fifteen participants were asked to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Channel-preserved feature vector compositions generated better performance than channel-averaged compositions in terms of classification accuracy and detection latency. Classification after averaging all channels have reportedly produced accuracies of 78% [22] and 65-75% [23]. This approach might be effective and useful for a BCI system with fewer channels that is only concerned with one cortical area.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Channel-preserved feature vector compositions generated better performance than channel-averaged compositions in terms of classification accuracy and detection latency. Classification after averaging all channels have reportedly produced accuracies of 78% [22] and 65-75% [23]. This approach might be effective and useful for a BCI system with fewer channels that is only concerned with one cortical area.…”
Section: Discussionmentioning
confidence: 90%
“…Although our single source-detector separation (SDS) of 3 cm could not filter out those extracerebral influences, it is unlikely that the inclusion of those extracerebral influences might compromise our study result. This is because the BCI study with a high-density multi-distance NIRS [23] showed that the use of multi-distance SDS NIRS improved accuracy by 5.2% compared to that of single SDS NIRS. Accordingly, it is inferred that our study results could be improved with a technique against the extracerebral contamination.…”
Section: Discussionmentioning
confidence: 99%
“…the market and their usefulness in NIRS-BCIs has been verified (Shin et al, 2017a;Kim et al, 2018;Kwon et al, 2018;Lancia et al, 2018). However, most of the new form factors adopted by the recent NIRS systems do not possess general applicability because they are designed to record hemodynamic changes from the prefrontal area only.…”
Section: Efforts To Improve the Performance Of Nirs-bcis: Future Persmentioning
confidence: 99%
“…However, in some cases it is not possible to achieve the required speed or accuracy of the control. Thus, existing neural interfaces based on electroencephalogram or fNIRS have a time resolution measured in seconds under optimal conditions [3], and are not suitable for direct control. To restore some possibilities of vision, the devices, that verbally describe objects appeared in front of a person, are recently developed [4].…”
Section: Wheelchair Control Systems Analysismentioning
confidence: 99%